2012
DOI: 10.1121/1.3672808
|View full text |Cite
|
Sign up to set email alerts
|

The influence of age and high-frequency hearing loss on sensitivity to temporal fine structure at low frequencies (L)

Abstract: Sensitivity to temporal fine structure (TFS) at low frequencies may be adversely affected by hearing loss at high frequencies even when absolute thresholds at low frequencies are within the normal range. However, in several studies suggesting this, the effects of hearing loss and age were confounded. Here, interaural phase discrimination (IPD) thresholds for pure tones at 500 and 750 Hz were measured for 39 subjects with ages from 61 to 83 yr. All subjects had near-normal audiometric thresholds at low frequenc… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

18
58
3

Year Published

2013
2013
2020
2020

Publication Types

Select...
9
1

Relationship

3
7

Authors

Journals

citations
Cited by 73 publications
(79 citation statements)
references
References 25 publications
18
58
3
Order By: Relevance
“…However, it does not fully account for the reduced HOB in NH am listeners. These older, NH adults may have suffered from a loss of binaural unmasking, consistent with recent reports of an age-related decline in the binaural processing of temporal envelope and fine structure (King et al, 2014;Moore et al, 2012;Hopkins and Moore, 2011) that reduced their HOB and their overall SRM.…”
Section: Group Differencessupporting
confidence: 70%
“…However, it does not fully account for the reduced HOB in NH am listeners. These older, NH adults may have suffered from a loss of binaural unmasking, consistent with recent reports of an age-related decline in the binaural processing of temporal envelope and fine structure (King et al, 2014;Moore et al, 2012;Hopkins and Moore, 2011) that reduced their HOB and their overall SRM.…”
Section: Group Differencessupporting
confidence: 70%
“…In the current study ITD500 did not correlate significantly with PTA LF or with audiometric threshold at 500 Hz (r ¼À0.05, p > 0.05). Whilst King et al (2014) found a moderate correlation between TFS-ITD detection and absolute threshold at the same carrier frequency, most others have not (LacherFougère and Demany, 2005;Hopkins and Moore, 2011;Strelcyk and Dau, 2009;Moore et al, 2012a). Whereas Neher et al (2011Neher et al ( , 2012 and Hopkins and Moore (2011) tested ITD detection in quiet, the current study tested ITD detection in noise.…”
Section: B Psychoacoustic Tasksmentioning
confidence: 93%
“…Also, sensitivity to ITDs tends to become poorer with increasing age, even when audiometric thresholds are normal or near-normal (Hopkins and Moore, 2011;Moore et al, 2012a;Moore et al, 2012b). This is important, since most users of hearing aids are older people.…”
Section: Introductionmentioning
confidence: 99%